2011
DOI: 10.1148/rg.315105735
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Sclerosing Disease: Autoimmune Pancreatitis and Extrapancreatic Manifestations

Abstract: Autoimmune pancreatitis is the pancreatic manifestation of IgG4-related sclerosing disease, which recently was recognized as a distinct disease entity. Numerous extrapancreatic organs, such as the bile ducts, gallbladder, kidneys, retroperitoneum, thyroid, salivary glands, lung, mediastinum, lymph nodes, and prostate may be involved, either synchronously or metachronously. Most cases of autoimmune pancreatitis are associated with elevated serum IgG4 levels; extensive IgG4-positive plasma cells; and infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
146
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 74 publications
5
146
1
10
Order By: Relevance
“…87,89,117 As explained earlier, the pathologic features of thyroid involvement are very similar to those of other organs affected in the systemic form of IgG4-RD, 90 especially autoimmune pancreatitis (as more than one-third of affected patients 118 have some form of thyroiditis as well), 90,119 and include diffuse lymphoplasmacytic infiltration, lymphoid follicle formation with germinal centers, dense stromal fibrosis, and follicular cell destruction (Figure 7, A through C). Increased numbers of IgG4-positive plasma cells are usually observed in IgG4-related thyroiditis 109,116 ( Figure 8, A through C).…”
Section: Igg4-related Thyroid Diseasesupporting
confidence: 54%
“…87,89,117 As explained earlier, the pathologic features of thyroid involvement are very similar to those of other organs affected in the systemic form of IgG4-RD, 90 especially autoimmune pancreatitis (as more than one-third of affected patients 118 have some form of thyroiditis as well), 90,119 and include diffuse lymphoplasmacytic infiltration, lymphoid follicle formation with germinal centers, dense stromal fibrosis, and follicular cell destruction (Figure 7, A through C). Increased numbers of IgG4-positive plasma cells are usually observed in IgG4-related thyroiditis 109,116 ( Figure 8, A through C).…”
Section: Igg4-related Thyroid Diseasesupporting
confidence: 54%
“…In addition, various types of lung involvement in IgG4-RD, including interstitial pneumonia, inflammatory pseudotumours and lymphadenopathy, have been described. [3][4][5][6][7] In contrast, the clinical characteristics of lung involvement in IgG4-RD, in particular the response to treatment and prognosis, remain unclear. In this study, we retrospectively evaluated the incidence and outcomes of lung involvement in 35 patients with AIP.…”
mentioning
confidence: 99%
“…Isolated strictures of the distal common bile duct also are common [21]. Placement of a temporary endoscopic biliary stent or percutaneous biliary drainage was performed in 26 patients (59%) to relieve jaundice [20]. According to the findings of the ERCP; the present case belongs to the group of isolated CBD stricture and placement of a plastic stent was successfully undertaken.…”
Section: Discussionmentioning
confidence: 88%
“…Valchou et al, in their study of IAC cases, found 43% of cases presenting with isolated extrahepatic bile duct involvement, and only 5% with intrahepatic bile duct involvement, while the copresentation was evident in 52%, and in 20% only the intra-pancreatic portion of the common bile duct was involved [20]. Isolated strictures of the distal common bile duct also are common [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation